Molecular Analysis and Bioinformatics Assessment of Full-Length L1 Gene of Bovine Papillomavirus Type-1 as a Potential DNA Vaccine Study - Hassan Hadi Abdul-Zahra; Yahia I. Khudhair; Husam Raheem Al-Hraishawi (Veterinary Medicine International)
Conclusions: The current investigation has provided crucial insights into BPV-1 type and diversity in the middle provinces of Iraq. These predominant strains have been identified and registered at NCBI for the first time. The amino acid mutations in the L1 protein have been highlighted. The conserved T- and B-cell epitopes that can detect BPV-1 type have been stablished. Finally, this project is the initial phase of creating a DNA-based vaccination for preventative and treatment purposes against BPV-related illnesses.